PERLINDUNGAN KONSUMEN TERHADAP PEREDARAN OBAT TRADISIONAL BERBAHAN KIMIA DI KOTA SAMARINDA DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Dezry Erzania Savira (Universitas 17 Agustus 1945 Samarinda, 2020)
Abstract Consumer protection is not only an individual problem, but it’s actually a common problem and national problem because basically everyone is a consumer. Meanwhile, protecting consumers is a matter of national law as well. Basically, talking about legal protection to consumers means we also talk about justice for everyone. In this modern era free trade tends to result in circulating goods and services that do not necessarily guarantee the security, safety and health of consumers. This condition is due to the condition of consumers who are on the weak side in dealing with business actors. This is because the level of consumer awareness and knowledge is still very low. One such business actor is a traditional drug manufacturer which neglects the health of consumers from the products they produce by adding chemicals that can be seen with the absence of a permit from BPOM. The purpose of this study is to determine the legal protection obtained by consumers against the circulation of traditional medicines made from chemicals and to determine the role of the Food and Drug Supervisory Agency to protect consumers against the circulation of traditional medicines made from chemicals in Samarinda City. This study uses empirical normative research methods with the problem approach used in this study is the statutory approach (statue approach) is a research that prioritizes legal material in the form of legislation as a basic reference in conducting research. Based on the results of the research it can be seen that the legal protection for consumers against the circulation of traditional medicines made from chemicals can be seen from article 4 of the Constitutuion Consumer Protection act states that Consumers are entitled to the right to comfort, security and safety, and the right to obtain correct, clear information, and be honest about the conditions and guarantees of goods and / or services. The role of BPOM to protect consumers against the circulation of traditional medicines made from chemicals is that BPOM has the right to withdraw traditional medicines made from chemicals from marketing and business operators may be subjected to administrative sanctions.Keywords : costumer protection, traditional medicine, and BPOM.